2009
DOI: 10.1007/s00520-009-0660-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in survivors of childhood cancer: a systematic review of the literature (2001–2008)

Abstract: Lack of comparability across studies remains a problem due to wide variation in study focus and designs. Conceptual and methodological issues include: use of numerous HRQOL and QOL measures, lack of distinction between conceptualization and measurement of HRQL and QOL, lack of initial qualitative input from survivors about QOL, little examination of the influence of environmental factors on QOL, little attention to survivors' satisfaction with life quality, use of small heterogeneous samples, and need for popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
83
2
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 51 publications
12
83
2
12
Order By: Relevance
“…Although reviews have been conducted on HRQOL issues for YASCC, these reviews were largely based on studies of quantitative design and were inclusive of studies conducted before the 21st century. 43,44 The present study highlights the unique contribution of qualitative methodology in the identification of HRQOL issues for YASCC and serves as an important supplement to the previous studies of quantitative design. The results are useful for revising the classical framework of HRQOL and related measurement instruments when applied to the YASCC population.…”
Section: Discussionmentioning
confidence: 76%
“…Although reviews have been conducted on HRQOL issues for YASCC, these reviews were largely based on studies of quantitative design and were inclusive of studies conducted before the 21st century. 43,44 The present study highlights the unique contribution of qualitative methodology in the identification of HRQOL issues for YASCC and serves as an important supplement to the previous studies of quantitative design. The results are useful for revising the classical framework of HRQOL and related measurement instruments when applied to the YASCC population.…”
Section: Discussionmentioning
confidence: 76%
“…At present, the results of studies on QoL in children surviving cancer are somewhat conflicting (Eiser et al, 2000;Baider et al, 1996;Zebrack and Zeltzer, 2003;Packer, 2008;Foster et al, 2009;McDougall and Tsonis, 2009;Sundberg et al, 2009;Zeltzer et al, 2009). While a number of studies have reported adverse outcomes (Grant et al, 2006;Speechley et al, 2006;Stam et al, 2006;Reinfjell et al, 2009;Gurney et al, 2009;Nathan et al, 2009;Hudson et al, 2003;Mulhern et al, 2004;Oeffinger et al, 2008), others have concluded that QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and psychosocial adjustment (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008) are satisfactory for the majority of long-term childhood cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, promoting resilience by recognizing and optimizing all these potential related variables, when possible, is a critical element of an integrative approach of cancer patients' psychosocial care. Finally, although most of the survivors appear to lead normal adult lives (e.g., achieving different educational degrees, good jobs, socio-familiar status, etc.,) there is also a small percentage of them who show some psychological problems such as anxiety, depression, fear of recurrence or related complications [1,2]. Thus, the proper evaluation of the cancer-related distress, or even posttraumatic distress symptoms, is required.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential and severe disturbances of the sequelae associated to cancer therapy, literature on the physical impact of cancer has grown rapidly in the last decades [2]. However, the mid and longterm psychological consequences of cancer also merit attention and their study has provided some contradictory results [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation